A Comprehensive Review of Rubia cordifolia Linn. - Deshkar, Nilambari; Tilloo, Shrikant; Pande, Vipinchandra (Pharmacognosy Reviews)
Rubia cordifolia Linn. (manjishtha) is popularly known as ‘Indian Madder’. Roots are traditionally used as anti-inflammatory, astringent, tonic, antiseptic, deobstruent, antidysenteric, blood purifier. It is an important ingredient of many ayurvedic preparations. The roots are natural red dye and are very effective in purifying blood. Various chemical constituents like anthraquinones, iridoid glycoside, naphthoic acid esters, bicyclic hexapeptides, and triterpenes have been isolated and identified from Rubia cordifolia Linn. The present review article is focused on phytochemical, pharmacological and other important aspects of manjishtha.
Keywords: Rubia cordifolia Linn; manjishtha; Rubiaceae; Indian Madder; anthraquinones